2019
DOI: 10.1021/acsami.9b13729
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Metallic V2O3@C for Advanced Aqueous Zinc-Ion Batteries

Abstract: Aqueous Zn-ion batteries (ZIBs) are a potential electrochemical energy storage device because of their highly intrinsic safety, low cost, and large capacity. However, it is still in the primary stage because of the limited selection of cathode materials with high rate and long-life cycling stability. In addition, the energy storage mechanisms of ZIBs have not been well established. In this work, we report the synthesis of porous V2O3@C materials with high conductivity and further illustrate its application as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 42 publications
3
136
0
Order By: Relevance
“…In addition to Zn 2þ intercalation mechanism in Na 2 V 6 O 16 •3H 2 O, a simultaneous H þ and Zn 2þ intercalation was observed in NaV 3 O 8 •1.5H 2 O. [45] Some other types of layered vanadates such as Zn 3 [49] V 2 O 3, [50] VO 2, [51,52] and VS 2 [53] were also reported with Zn 2þ ion storage behaviors in aqueous Zn batteries.…”
Section: Vanadium-based Oxidesmentioning
confidence: 90%
“…In addition to Zn 2þ intercalation mechanism in Na 2 V 6 O 16 •3H 2 O, a simultaneous H þ and Zn 2þ intercalation was observed in NaV 3 O 8 •1.5H 2 O. [45] Some other types of layered vanadates such as Zn 3 [49] V 2 O 3, [50] VO 2, [51,52] and VS 2 [53] were also reported with Zn 2þ ion storage behaviors in aqueous Zn batteries.…”
Section: Vanadium-based Oxidesmentioning
confidence: 90%
“…[ 221 ] Up to date, conductive carbon coating has attracted more research attention in energy storage and conversion fields when compare with conductive polymer coating. In the studies of AZIBs, many types of cathode materials modified by carbon coating have been reported, such as α‐MnO 2 @C, [ 222 ] δ‐MnO 2 @CAC, [ 223 ] MnO 2 @CC, [ 145 ] MnO x @CNF, [ 224 ] V 2 O 3 @C, [ 225 ] Mn 3 O 4 @N doped carbon matrix nanorods (Mn 3 O 4 @NC Nrs), [ 84 ] and so on. To deep understanding how does the carbon coating improve the electrochemical performance of cathodes, here, a typical case is given.…”
Section: Structural Engineering For Cathode Materialsmentioning
confidence: 99%
“…V 2 O 3 with a tunneled structure has been studied and applied in many high-tech fields, like photocatalysis, supercapacitors, battery, and so on [104][105][106][107]. Hua et al [43] fabricated V 2 O 3 nanowire arrays by reducing NH 4 V 4 O 10 nanoarrays under a flow of 5% H 2 /95% Ar and then tested as the cathode for Li-ion battery.…”
Section: Omentioning
confidence: 99%